INOVASI METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA - Husaini, Muhamad; Anwar, Ahmad; Nadifah, Nurul Ahilatun (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
Learning achievement is achieved through well-conceptualized learning planning and requires innovations in the implementation of teaching and learning. This research is qualitative descriptive research and library research(library research) data comes from various reading sources, book articles and other sources. the research results are:PAI learning method innovations have an important role in improving student learning achievement in schools. So innovation will be seen in the achievements achieved by students, both in academic and non-academic fields. Innovation in learning methods applied in schools is carried out in an evolutionary (gradual) manner. Schools that implement a full day school learning system, taking into account the length of study time at school